Treatment of Neurological Diseases in Pakistan and Medicinal Plants - Letter to Editor - Wasim Ahmad; Syed Hussain Baqar Abidi (Gandhara University, 2023)
In developing and developed countries, neurological diseases contribute to the major reason for morbidity and mortality. The overall burden is 6.5% globally, of which advanced countries contribute 10 to 11%, whereas progressive countries constitute 4 to 5%. The higher ratio in technologically advanced countries might be due to their advanced system providing complete patient data. Some neurological diseases are common and wellestablished, whereas others occur rarely or are poorly ordered. Schizophrenia affects 45 million people, whereas depression affects 340 million globally. The people living with Alzheimer's constitute 11 to 45 million people, accounting for 1% of the total disease load. 10% Pakistani community suffer from mental disorders, with 1% Alzheimer's, 5% depression, 2% epilepsy and 1.5% schizophrenia. Medicinal plants play a vital role in treating several neurological disorders. Due to the upsurge in the cost of the available drugs, the local population is dependent on the use of medicinal plants to treat these neurological disorders. Medicinal plants possess a great therapeutic potential and fewer side effects than synthetic drugs. In Pakistan, research on medicinal plants is increasing day by day. The Pakistani population traditionally depends on herbal medications to treat several neurological disorders. The use is more in rural areas due to easy access and costeffectiveness. In Pakistan, there is a stern gap between the availability of neurological care and a trained neurologist. In this scenario, the use of traditional medicinal plants for aiming to treat neurological disorders is obvious.